Association of Self-Reported Weight Change and Quality of Life, and Exercise and Weight Management Behaviors Among Adults with Type 2 Diabetes Mellitus: The SHIELD Study - Susan Grandy; Kathleen M. Fox; Debbra D. Bazata (Cardiology Research and Practice)
Purpose. This study examined the association between self-reported weight change and quality of life, and exercise and weight management behaviors among individuals with type 2 diabetes mellitus (T2DM). Methods. In the US SHIELD study, respondents reported whether they had lost or gained weight compared with 1 year earlier and completed the SHIELD-WQ-9 quality of life questionnaire as well as provided information on their exercise and weight management behaviors in the past 12 months. Results. Sixteen percent of the respondents reported gaining weight (n=460), and 30% reported losing weight (n=895). More respondents who reported losing weight exercised regularly, limited calorie and fat intake, and increased fiber, fruit, and vegetable intake compared with respondents who reported gaining weight (P<0.01). For all nine aspects of daily life, a significantly greater proportion of respondents who reported losing weight reported improved well-being (12%–44%) compared with respondents who reported gaining weight (P<0.0001). Conclusions. Self-reported weight loss was associated with improved well-being, better exercise, and weight management behaviors among individuals with T2DM.